Effectiveness of folic acid in unexplained infertility - Jadhav, Sujata Narendra; Pitale, Devdatt Laxman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Folic acid is commonly used by infertile women worldwide. However, studies on the effect of folic acid in women with unexplained infertility are lacking. This aim of this study was to evaluate the effectiveness of folic acid in women with unexplained infertility. Methods: This prospective multicentric study was performed from June 2019 to July 2020 in women with unexplained infertility attending the fertility clinic. In this study, 50 women with unexplained infertility who satisfied the inclusion and exclusion criteria were started on folic acid therapy. The effectiveness of therapy was evaluated on the basis of successful conception and adverse effects if any. Results: Folic acid therapy showed a marked improvement in infertility status measured in terms of successful conception. After initial 12 weeks therapy successful conception was achieved in 40 (80%) women without any adverse effects. Conclusions: Folic acid supplementation has a positive effect on pregnancy outcome in women with unexplained infertility without any adverse effects. Folic acid is thus a safe and cost-effective option in women with unexplained infertility.